Financial reporting and analysis - Dunn, John, 1959- (Hoboken, N.J. : Wiley, 2010)
The book describes the logic and history of the development of accounting standards , enabling the reader to fully appreciate the effects of these rules. It covers the mechanics of applying the rules but it also examines the compromises and loopholes that have arisen because of the political processes inherent in the standard setting processes.
Published accounts -- Overview of regulation -- Form and content of an annual report -- Academic research and reporting regulation -- The conceptual framework -- Reporting tax -- Reporting earnings and earnings quality -- Accounting for property, plant and equipment -- Accounting for intangibles -- Accounting for inventory -- Accounting for liabilities -- Introduction to consolidation -- The mechanics of consolidation -- In summary.
Includes bibliographical references and index.
opc 12/06/13
Loans
Keywords: Financial statements; Corporations -- Accounting